The trend of teachers of the Arabic language towards electronic education in the preparatory stage - Al-Mousawi, Taghreed Dinar Sihoud; Al-Obaidi, Ruqayya Abdul-Imam Abdullah (Al-Adab Journal, 2022)
This research aims to achieve the objectives: 1- What is the trend of teachers of the Arabic language in the preparatory stage towards e-learning?2- Is there a statistically significant difference in the direction of Arabic language teachers towards e-learning due to the gender variable?To achieve these goals, the researcher used a descriptive research method. The community of its research has identified Arabic language teachers and female teachers for the preparatory and secondary stage of the day-to-day government (boys - girls), affiliated to the sub-directorates of Wasit Governorate Education (Al-Kut, Al-Markaz, Al-Hay, An-Numaniya, Al-Aziziyah, Al-Suwairah). 191 teachers and 129 schools. To achieve the goal of the research, the researcher prepared a measurement tool, namely:The trend scale for teachers of the Arabic language in the preparatory stage, consisting of (44) paragraphs, and the validity of the scale was confirmed, by presenting it to a group of experts (apparent validity), as well as extracting the validity of the construction, and making sure of its stability in the way (Fakronbach), and it reached (0.747) ) Which is a good reliability coefficient with which the reliability of the scale can be trusted.After completing the research tool, the sample was applied to the sample of statistical analysis (220) teachers and schools, and all the paragraphs had the psychometric characteristics of (validity and reliability) and none of them were omitted, so the researcher applied to the basic research sample of (100) teachers and schools after adding the statistical analysis sample. So that the total of the sample is (320) teachers and schools, which is the amount of the community itself, distributed among the middle and high school daytime schools in Wasit Governorate, and after processing the data statistically using the arithmetic mean law, the Pearson correlation coefficient, and the t-test for a sample to reveal the significance of the differences in the correlation between the trend towards e-learning At the teachers of the Arabic language and its teachers in the preparatory stage. The results of the statistical analysis showed the following:1- The teachers of the Arabic language enjoy an orientation towards e-learning.2- There are no statistically significant differences in the trend scale due to the gender variable. In light of the results of the research, the researcher recommended that institutions take the development of the teacher in them by motivating them in their direction towards e-learning, so that he can accomplish his work and tasks and perform the future roles expected of him, developing the programs used in the work of the educational process. To complete and develop this study, the researcher proposes to conduct a number of studies aimed at:1- The level of trend towards e-learning among faculty members of various universities and colleges in Iraq is known.2- Conducting a study aimed at comparing Arabic language teachers and other specializations in the extent of their orientation towards e-learning.3- Conducting a comparative study between teachers of Arabic language and teachers of other specializations regarding the variable of orientation towards e-learning.